Spray Deposition and Control of Botrytis cinerea on Grape Leaves and Bunches: Part 2 (Wine Grapes) - Brink, J.C.; Calitz, F.J.; Fourie, P.H. (South African Journal of Enology and Viticulture, 2016)
Poor control of fruit and foliar diseases in vineyards is often attributed to insufficient spray deposition of susceptible tissue. To optimise spray deposition, a deposition assessment protocol using fluorometry, photomicrography and digital image analyses was developed to determine minimum spray deposition quantity and quality levels needed for effective B. cinerea control in wine grapes (Chenin blanc). Leaves and bunches were sprayed at different growth stages with different volumes of a mixture of fenhexamid and fluorescent pigment. Pigment deposition quantity and quality were determined from photos of pedicels and leaves taken with a digital camera under a stereo microscope and black light illumination at ×30 and ×10 magnification, respectively. After inoculation with dry airborne conidia of B. cinerea infection levels on pedicels, receptacles and leaves were determined and infection levels and deposition data were subjected to sigmoidal and Hoerl regression analyses, respectively. From these biological efficacy curves the deposition levels that affected 75% control of B. cinerea infection (FPC75 values) were calculated for leaves and for each growth stage for pedicels and receptacles. Deposition measurements on sprayed leaves and bunch parts correlated favourably with Botrytis infection levels. An increase in spray volume resulted in higher deposition quantity and improved quality values with a reduction of B. cinerea infections. However, at a certain point, deposition quality remained constant and infection levels did not decrease significantly with increasing spray volume. Susceptibility of pedicels and receptacles to B. cinerea decreased with maturity. FPC75 values can be used as benchmarks to evaluate spray application in wine grape vineyards.